2019
DOI: 10.1007/s10681-019-2347-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bermudagrass (Cynodon dactylon L.) germplasm for nitrogen use efficiency

Abstract: Bermudagrass is the most important warm-season pasture in the Southern USA with exceptional forage production potential and abiotic stress tolerance. However, it requires high nitrogen (N) supply to reach its full biomass and quality potential. Our objectives were to: (1) develop a nitrogen use efficiency (NUE) screening protocol for bermudagrass in controlled or semi-controlled conditions, (2) identify contrasting genotypes for NUE from natural variants and, (3) develop a knowledge base of NUE in bermudagrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…In the southeast of the USA, different cultivars of bermudagrass have shown good potential for this purpose. However, differences in the nitrogen use efficiency among cultivars have been found [42]. Previous studies have shown annual uptake values for this species in the range of 314 to 382, and 44 kg ha −1 yr −1 of N and P, respectively.…”
Section: Soil Nutrientmentioning
confidence: 86%
See 2 more Smart Citations
“…In the southeast of the USA, different cultivars of bermudagrass have shown good potential for this purpose. However, differences in the nitrogen use efficiency among cultivars have been found [42]. Previous studies have shown annual uptake values for this species in the range of 314 to 382, and 44 kg ha −1 yr −1 of N and P, respectively.…”
Section: Soil Nutrientmentioning
confidence: 86%
“…Therefore, it is necessary to manage the paddock in such a way that those service areas can be buffered by grassed areas to minimize runoff and erosion. The morphological and physiological traits of bermudagrass, a warm season perennial species adapted to different types of soils and climates, that shows aggressive growth, good grazing tolerance, and ability to produce biomass of good quality forage when soil nutrients are not limiting [42], make this grass suitable for this kind of systems. Its growth habit and reproductive mechanisms (rhizomes, stolons, and extensive root mass) allowed it to endure the grazing, rooting, trampling and lounging behaviour of the sows, and to recover during the rest periods between successive grazings.…”
Section: Ground Covermentioning
confidence: 99%
See 1 more Smart Citation
“…Schneider-Canny et al [ 30 ] also reported the limitation of smaller pots in bermudagrass. Since higher plant mass per pot volume decreases plant growth and can affect differences between treatments, proper pot size is important [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…En estudios realizados en zonas tropicales y subtropicales se ha encontrado que el pasto estrella presenta buen potencial de crecimiento, rendimiento y calidad nutritiva para la producción láctea, manejando los días adecuados de rotación y recuperación en conjunto con la fertilización, para optimizar su rendimiento, calidad y persistencia (López et al, 2010;Yong et al, 2012;Villalobos y Arce, 2013;2014). Las especies de pasto Cynodon son de metabolismo fotosintético C 4 , por lo que pueden acumular mayor materia seca en relación a los pastos C 3 , se cultivan ampliamente en zonas tropicales y subtropicales, y responden a la fertilización nitrogenada para incrementar el rendimiento y calidad nutritiva (Yong et al, 2014;Cristiano et al, 2015;Taffarel et al, 2016;Borges et al, 2017;Schneider et al, 2019).…”
Section: Introductionunclassified